Thinking orientation and overconfidence: a newsvendor study - Wiesner, Julian; Đula, Ivan; Größler, Andreas (Frontiers in Behavioral Economics, 2024)
This study uses the newsvendor problem to investigate the correlations between thinking orientation, overconfidence, and the economic outcome. We aim to shed light on possible interconnections between these variables and extend the existing conceptual models of thinking orientation and overconfidence. To test the conceptual model and the corresponding hypotheses empirically, we employed a laboratory experiment with 50 hypothetical decision periods in which 142 participants ordered a highly profitable product. We found compelling evidence suggesting overprecision as the mediating variable between thinking orientation and the economic outcome. Furthermore, this research offers some practical implications.